2020
DOI: 10.3892/ol.2020.11289
|View full text |Cite
|
Sign up to set email alerts
|

IRF1 association with tumor immune microenvironment and use as a diagnostic biomarker for colorectal cancer recurrence

Abstract: Colorectal cancer (CRC) is considered to be one of the most lethal cancer types globally, and its recurrence is a major treatment challenge. Identifying the factors involved when determining the risk of CRC recurrence is required to improve personalized therapy for patients with CRC. Based on the GSE39582 dataset, the present study demonstrated that a higher ratio of M1 macrophages and activated memory CD4 + T cells indicated a better recurrence-free survival (RFS) time for CRC, using CIBERSORT and Pearson's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…P2RY13 is a G-protein-coupled receptor, and it was reported to be decreased upon epidermal growth factor (EGF)- and hypoxia-induced epithelial–mesenchymal transition (EMT) in breast cancer cells ( 57 , 58 ). Additionally, P2RY13 was also involved in the identification of M1 macrophages in CRC ( 59 ). However, multivariate Cox analysis showed that only T stage, N stage, and CX3CR1 were independent risk factors that could affect the prognosis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…P2RY13 is a G-protein-coupled receptor, and it was reported to be decreased upon epidermal growth factor (EGF)- and hypoxia-induced epithelial–mesenchymal transition (EMT) in breast cancer cells ( 57 , 58 ). Additionally, P2RY13 was also involved in the identification of M1 macrophages in CRC ( 59 ). However, multivariate Cox analysis showed that only T stage, N stage, and CX3CR1 were independent risk factors that could affect the prognosis of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…These results were analyzed by long-rank test. The correlation between 24 hub genes and 22 immune cells was determined using Person's correlation analysis and CIBERSORT to reveal the relationship between hub genes and immune cells (17). Afterward, comprehensive correlation analysis between six selected survival-related hub genes and tumor-infiltrating immune cell signatures for GBM were performed using Tumor Immune Estimation Resource (TIMER 1.0, https://cistrome.shinyapps.…”
Section: Identification and Immune Infiltration Of Survival-related Hmentioning
confidence: 99%
“…The anti-tumorigenic role of interferon regulatory factor 1 (IRF1) has been reported in several types of cancer, by regulating genes related to PD-L1, DNA damage, apoptosis, and lymphocyte differentiation, also interacting multiple signaling pathways (Forero et al, 2019;Huang et al, 2019;Ohsugi et al, 2019;Wu et al, 2020). Moreover, IRF1 expression in tumor cells was also reported to be critical for the immune response to adoptive T cell therapy, as well as macrophage infiltration and memory CD4 + T cell activation (Wu et al, 2020). Zhang et al found that Manic Fringe (MFNG) was highly expressed in Claudin-low breast cancer and functioned as an oncogene by activating Notch signaling, thereby promoting tumor cell migration, tumorsphere formation, and epithelial-to-mesenchymal transition (EMT) (Zhang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%